Žodžio pradžios s ir š pakaitos lietuvių kalbos tarmėse - Grinaveckis, Vladas (Kalbotyra, 1995)
There are cases when the same words in different dialects of Lithuanian begin with either s- or š-, e.g. skurlis is škurlis ‘skuduras’. Also sometimes this alternation of the initial s- and š- is found in one and the same dialect, e.g. škypas is skypas ‘įkypas’, šiundyti is siundyti, or in the cases when in the dialect, alongside with the available variants with the initial s- and š- the variants without them are also used, e.g. smūksoti, šmukšoti, mūksoti ‘the zero variant, murksoti’. Such phonomorphological alternation of the initial part of the word we consider to be a novel phenomenon in Lithuanian. In the suggested glossaries of such alternation the first place is allotted to the variants of these words with the suspected new initial s- and š-.